DIMENSIONS OF SOCIAL CAPITAL - N. S. Seliverstova; E. L. Iakovleva; O. V. Grigoryeva; L. V. Vorontsova (Russian Journal of Economics and Law, 2018)
Objective: to describe the manifestations of social capital in the context of the main factors affecting its formation, which will enable to systematize the existing ideas about the dimensions of social capital.Methods: abstract-logical and dialectical, phenomenological methods.Results: social capital is an important concept in the economic system, but it is difficult to identify and measure. The article analyzes the phenomenon of social capital, as well as approaches to its definition. Based on the literature analysis, five sections are identified in which the concept of social capital is characterized. It is shown that the institutional environment is the basis for the formation of social capital. It is revealed that the individual qualities of a personality can both contribute (emotional intelligence, etc.) and prevent (closeness for communication, inability to listen, conflict-generating character, etc.) the accumulation of social capital. The content of the concept of family social capital is shown. The predominant influence of social capital on the development of small firms in comparison with medium and large organizations is revealed. The influence of civic activity on economic development through social capital is studied.Scientific novelty: five dimensions of social capital are identified: 1) social capital and individual qualities of personality;2) social capital and family ties; 3) social capital and corporate culture; 4) social capital and civic activity; 5) social capital and institutional environment. It is determined how these patterns affect economic development.Practical significance: the understanding of the main dimensions of social capital revealed in the work makes it urgent to identify the structure of social capital, and creates a basis for further research in this area.